Exploring the limits of the tunnel junction fabrication technique for Josephson junctions TWPA and the preliminary characterisation results - Navarro Montilla, J; Driessen, EFC; Barbier, A; Boussaha, F; Chaumont, C; Tan, B-K (International Symposium on Space Terahertz Technology, 2024)
Travelling Wave Parametric Amplifiers (TWPAs) can potentially achieve quantum limited noise over a broad bandwidth in the microwave regime, with potential applications in the readout of millimetre (mm) and sub-millimetre (sub-mm) receivers to further improve the system sensitivity, among many other applications. TWPAs using embedded Josephson junctions (J-TWPA) have proven to exhibit noise performance approaching the quantum limit, however its compression point (P–1dB ~ –100 dBm) is too low for reading out mm and sub-mm astronomical receivers. Therefore, we explored the design of higher dynamic range JTWPAs to match the power requirements, and to optimise the performances of the JTWPA for this specific application. Our aim is to adapt the well-established Nb-AlOx-Nb tri-layer fabrication technique used routinely for developing high-quality Superconductor-Insulator-Superconductor (SIS) tunnel junctions to fabricate our JTWPA. Therefore, we present in this paper our investigation of the feasibility of such technique in fabricating large number of lower critical current density junctions embedded in a coplanar waveguide (CPW). The preliminary results on a 500-junctions device are in line with the expected behaviour, showing a measured gain consistent with theoretical calculations which demonstrates the potential use of the tri-layer tunnel junction technology for the fabrication of JTWPAs.